Pengaruh Kualitas Pelayanan Dan Fasilitas KesehatanTerhadap Kepuasan Pasien Rawat Inap PadaRumah Sakit Umum Bunda Jakarta - Irna Rosdiana; Aris Hidayat; Diana Tambun (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to determine the effect of service quality and health facilities on inpatient satisfaction at Bunda General Hospital Jakarta. The population and research sample were 127 respondents. The sampling technique used Purposive Sampling technique (purposive sample). Data processing in this study used the SPSS (Statistical Package for Social Science) software programme version 26.0. The research method uses a type of quantitative method research through an associative approach. The results of the study on the Service Quality variable (X1) show the results that there is an effect of service quality on patient satisfaction. Based on the results of the t test (partial test) which shows the value of tcount> ttable and significant <0.05, namely; 4.106> 1.979 and significant 0.000 <0.05. In the Health Facility variable (X2) shows the results that there is an effect of health facilities on inpatient patient satisfaction at Bunda General Hospital Jakarta. Based on the results of the t test (partial test) which shows the value of tcount> ttable and significant <0.05, namely; 6,730> 1,979 significant 0.000 <0.05. Simultaneously shows the results of the effect of service quality and health facilities on inpatient patient satisfaction at the Jakarta General Hospital. Based on the results of the F test (simultaneous test) which shows the value of Fhitung> Ftabel and significant <0.05, namely; 160.527> 3.07 and significant <0.05, namely; 0.000 <0.05.